Factors Affecting Compliance with Professional Ethics among Accountants in Pathum Thani Province, Thailand - ปารวัตร์, กิตติวรรณ์; สุขเฉลิม, ณัฏธิตา; ทิพย์ดัด, ณิชกานต์; เผือกสีสุก, พิมพ์ประกาย; อิมะไชย์, วรรณภา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) examine the level of professional ethical practice among bookkeepers in Pathum Thani Province; 2) compare the level of professional ethical practice classified by personal factors; and 3) investigate organizational factors affecting professional ethical practice among bookkeepers. The study employed a quantitative survey research design. Data were collected through questionnaires from 355 bookkeepers in Pathum Thani Province using simple random sampling. Statistical analyses included percentage, mean, standard deviation, t-test, F-test, and multiple regression analysis (MRA).          The findings revealed that: 1) overall and dimensional levels of professional ethical practice among bookkeepers in Pathum Thani Province were at the highest level. Among the dimensions, integrity ranked highest, followed by transparency in reporting, compliance with standards, objectivity, professional competence and professional behavior, and confidentiality. 2) The comparative analysis indicated that bookkeepers with different ages, work experiences, and educational levels demonstrated significantly different overall levels of professional ethical practice at the .05 level of statistical significance. 3) Organizational factors significantly affecting professional ethical practice among bookkeepers at the .05 level included internal control, management expectations, and organizational policies.